Symplectite and kelyphite formation during decompression of mafic granulite from Gjelsvikfjella, central Dronning Maud Land, Antarctica - Elvevold, Synnøve; Jacobs, Joachim; Pedersen, Leif-Erik Rydland; Sunde, Øyvind; Engvik, Ane K.; Myhre, Per Inge (European Journal of Mineralogy, 2023)
Central Dronning Maud Land (cDML) is part of the late Mesoproterozoic Maud Belt in East Antarctica, which was metamorphosed and deformed during the Ediacaran–Cambrian Gondwana assembly. Here we study high-pressure (HP) mafic rocks in Gjelsvikfjella, cDML, which occur as lenses and pods transposed in highly strained, upper amphibolite-facies gneisses. We present a P – T – t history for the HP rocks based on mineral assemblages, reaction textures and new U–Pb zircon data. Relics that indicate an early HP granulite-facies stage have been identified in anhydrous garnet–clinopyroxene rocks. The peak-pressure assemblage was plagioclase-free and contained garnet, titanite, clinopyroxene and quartz. The HP assemblage has been extensively overprinted by lower-pressure phases and exhibits a variety of symplectite and corona textures that record the post-peak-pressure evolution of the rocks. Decompression and heating in the granulite-facies field resulted in the replacement of titanite by ilmenite–clinopyroxene symplectite, formation of clinopyroxene–plagioclase intergrowths and resorption of garnet by plagioclase–clinopyroxene kelyphite. Formation of late orthopyroxene in symplectites and kelyphites demonstrates that the P – T evolution entered the medium-pressure granulite-facies field. The peak metamorphic stage was followed by retrograde cooling into the amphibolite facies. In situ laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) U–Pb dating of zircons indicate Mesoproterozoic protolith ages (1150–1000 Ma) and Ediacaran–Cambrian metamorphic reworking at ca. 568 and ca. 514 Ma. The HP granulites were formed and exhumed during a clockwise P – T evolution related to continental collision during Gondwana amalgamation, followed by post-collisional extension and orogenic collapse.